2017
DOI: 10.1007/s13555-016-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Psychological Impact of Skin Conditions

Abstract: Skin conditions such as psoriasis, eczema, and skin cancer often have a substantial psychologic and social impact on our patients. Some of these patients limit their life because they feel self-conscious about their symptoms. Sometimes, greater life satisfaction comes from accepting that perhaps some symptoms will remain or recur, even in an individual who responds well to treatment. This acceptance involves acknowledging the existence of symptoms, thereby allowing the patient to pursue a meaningful life that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 6 publications
1
30
0
3
Order By: Relevance
“…The inconveniences, fear, and the sadness of stigmatization due to the visibility of the skin disease (unpleasant remarks, being teased/bullied, social exclusion) were shared by most. The same was evident in earlier research into appearance-related conditions ( Lovegrove and Rumsey, 2005 ; Magin et al, 2008 ; Rumsey Harcourt, 2004 ; Tuckman, 2017 ). These sequelae of NS hamper children and adults in their emotions, behavior, self-esteem, and social contacts.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The inconveniences, fear, and the sadness of stigmatization due to the visibility of the skin disease (unpleasant remarks, being teased/bullied, social exclusion) were shared by most. The same was evident in earlier research into appearance-related conditions ( Lovegrove and Rumsey, 2005 ; Magin et al, 2008 ; Rumsey Harcourt, 2004 ; Tuckman, 2017 ). These sequelae of NS hamper children and adults in their emotions, behavior, self-esteem, and social contacts.…”
Section: Discussionsupporting
confidence: 79%
“…Compared with the general population, patients with these skin diseases indicated reduced well-being, quality of life, and psychological problems like anxiety and depression ( Dures et al, 2001 ; Lewis-Jones and Finlay, 1995 ; Verhoeven et al, 2007 ). The psychosocial impact due to visibility like bullying, social exclusion, fearful anticipation in social activities, emotional burden, and shame due to a deviant appearance also has been described by Lovegrove and Rumsey (2005) , Magin et al (2008) , Rumsey and Harcourt (2004) , and Tuckman (2017) . A study in families of patients with atopic dermatitis showed that the quality of life was affected by the increasing disruption of family functions, affecting family dynamics and family life in general ( Shobaili, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of skin lesions or chronic progression of skin conditions may adversely affect quality of life 1 . Studies have shown that those with visible dermatologic conditions consistently report poorer quality of life and psychosocial functioning 7 . Additionally, adverse drug reactions can cause psychiatric and dermatologic symptoms 1 .…”
Section: The Bidirectional Relationshipmentioning
confidence: 99%
“…1 Studies have shown that those with visible dermatologic conditions consistently report poorer quality of life and psychosocial functioning. 7 Additionally, adverse drug reactions can cause psychiatric and dermatologic symptoms. 1 Corticosteroids may trigger psychotic symptoms 1 and antipsychotics such as Olanzapine may cause Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS).…”
mentioning
confidence: 99%
“…Ahora bien, el hecho de no encontrar asociación estadística entre este tipo de cánceres y la patología psiquiátrica no significa que no existan pacientes en los que este tipo de lesiones provoquen alteraciones emocionales 18 . En aquellos casos en los que esto ocurre, las preocupaciones que suelen tener los pacientes se recogen en la tabla 3.…”
Section: Tabla 2 Prioridades Vitales De Las Personas Según El Grupo unclassified